Disputing “Gender” in Academia: Illiberalism and the Politics of Knowledge - Ergas, Yasmine (2022)
This article explores the attacks to which gender studies programs in Central and Eastern Europe have been subject and the responses such attacks have elicited in the context of analogous phenomena in other parts of the world. The undermining of gender studies in recent years has been aggravated by the effects of the Covid‐19 pandemic that has exacerbated financial crises of educational institutions while also—in some contexts—providing cover for restrictions on academic freedom. Our specific focus here, however, is on how illiberal policies have limited the scope of academic gender studies, sometimes calling into question their very existence. To identify the modalities through which illiberal governments may narrow gender studies programs, we draw on Pirro and Stanley’s analysis of illiberal policymakers’ toolkit based on “forging,” “breaking,” and “bending.” We consider these categories useful for our analysis but add a fourth: “de‐specification”—a purposeful submersion, or redefinition, of gender studies into other programs, such as family studies. Our purpose is not to present an exhaustive analysis but rather to delineate a framework for analyzing such attacks and the responses to which they have given rise, and then to indicate some questions for further research. As such, this article should be read as a work in progress that seeks to explicate the modalities of the attacks on gender studies in higher education to which contemporary illiberalism has given rise concomitantly with attacks on gender rights and emerging forms of resistance that bespeak the resilience of the gender academy.